Numerical analysis of glued laminated timber beams reinforced by Vectran fibers - Mascia, Nilson Tadeu; Bertoline, Carlos Augusto Abade; Baságlia, Cilmar Donizeti; Donadon, Bruno Fazendeiro (Ambiente Construído, 2018)
<span style="font-family: ’Times New Roman’,serif; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">Some factors, such as environmental actions and load increases, can cause a necessity to restore a structural element. An efficient method typically used is to reinforce the structure with a high mechanical property´s material. In this study, a numerical approach of glued laminated timber beams reinforced with the following synthetic fibers: Vectran®, carbon and glass fibers was developed.Vectran® fibers have high performance and are employed in various areas, but not yet as a structural reinforcement. The beam models were designed on Ansys software-version 12 and the results were analyzed regarding the maximum stresses and displacements. When compared to unreinforced beam, the fiber reinforcement absorbed a great part of the acting stresses, reducing the tensile stress and the displacement maximum values. Considering mechanical properties and the material cost, Vectran® fiber is an interesting alternative for structural reinforcement, fitting its mechanical performance at an intermediate level between carbon fiber and glass fiber.